Oncological outcomes after robot‐assisted radical prostatectomy: long‐term follow‐up in 4803 patients. (December 2014) - Sukumar, Shyam; Rogers, Craig G.; Trinh, Quoc Dien; Sammon, Jesse; Sood, Akshay; Stricker, Hans; Peabody, James O.; Menon, Mani; Diaz‐Insua, Mireya
<x xml:space="preserve">Abstract</x> Objective To evaluate oncological outcomes in patients undergoing robot‐assisted radical prostatectomy (RARP) at a high‐volume tertiary centre with focus on biochemical recurrence (BCR); previous studies on oncological outcomes for patients undergoing RARP for prostate cancer are limited to small series. Patients and Methods In all, 5152 consecutive patients underwent RARP from 2001 to 2010; 4803 patients comprised the study cohort after exclusions. BCR was defined as a serum prostate‐specific antigen (PSA) level of ≥0.2 ng/mL with a confirmatory value. BCR‐free survival (BCRFS), metastasis‐free survival (MFS) and cancer‐specific survival (CSS) were estimated using the Kaplan–Meier method and Cox hazards regression models were generated. Results The mean preoperative PSA level was 6.1 ng/mL, pathological Gleason grade and stage were ≥7 in 68% and ≥pT3 in 34% of patients. There was BCR in 470 patients (9.8%), 31 patients developed metastatic disease (0.7%) and 13 patients died from prostate cancer (0.3%) during a mean (range) follow‐up of 34.6 (1–116.7) months. Actuarial 8‐year BCRFS, MFS and CSS were 81%, 98.5% and 99.1%, respectively. In patients with node‐positive disease, actuarial 5‐year BCRFS, MFS, and CSS were 26%, 82%, and 97%. For organ‐confined disease, predictors of BCR included pathology Gleason grade (primary Gleason 5 vs 3, hazard ratio [HR] 5.52, P = 0.018; Gleason 4 vs 3, HR 1.97, P = 0.001), preoperative PSA level (10–20 vs ≤10 ng/mL, HR 2.38, P = 0.001), and surgical margin status (positive vs negative, HR 3.84, P < 0.001) Conclusions RARP appears to confer effective long‐term biochemical control. To our knowledge, this is the largest report of oncological outcomes in a RARP series to date.